Professional Windows 7 development guide - Mueller, John, 1958- (Wrox professional guides., 2011)
Describes the features of Windows 7, covering such topics as security policies, Windows Firewall, user account control, the Ribbon, libraries, Windows PowerShell, and 64-bit programming.